Implementasi PBL dan GNM Disertai Permainan Cublak-Cublak Suweng untuk Meningkatkan Aktivitas dan Keterampilan Pada Pembelajaran IPAS Peserta Didik Kelas IV SDN Simpang Empat Kabupaten Banjar - Didi Dwi Hermawan; Zain Ahmad Fauzi (Lembaga Bale Literasi, 2026)
The background of this study is the low level of student participation, critical thinking skills, and collaboration abilities, as well as suboptimal learning outcomes in IPAS, particularly in IPS material. This condition is caused by the dominance of one-way teaching methods, limited innovative learning models and media, and minimal opportunities for students to discuss, collaborate, and actively participate. To address these problems, the Problem Based Learning (PBL) model was implemented, combined with the GNM model (Group Investigation, Numbered Heads Together, and Mind Mapping) and the traditional game Cublak-Cublak Suweng. This study is a Classroom Action Research (CAR) conducted over three meetings with 20 fourth-grade students at SDN Simpang Empat, Banjar Regency, in the even semester of the 2023/2024 academic year. Data were collected in both qualitative and quantitative forms through observations of teacher activities, student activities, critical thinking skills, collaboration skills, and learning outcomes. The success criteria were set if at least 80% of students were categorized as “Very Active” and 80% achieved scores ?72. The results showed improvements from the first to the third meeting, where teacher and student activities reached the “Very Good” and “Very Active” categories, critical thinking and collaboration skills improved to “Very Skilled,” and the learning completeness reached 85%. Therefore, the implementation of PBL combined with GNM and traditional games has proven effective in enhancing the quality of IPAS learning